Risk perception and terrestriality in primates: a quasi‐experiment through habituation of chacma baboons (Papio ursinus) in Gorongosa National Park, Mozambique - Hammond, Philippa (2022)
Objectives Habituation is a common pre-requisite for studying noncaptive primates. Details and quantitative reporting on this process are often overlooked but are useful for measuring human impact on animal behavior, especially when comparing studies across time or sites. During habituation, perceived risk of a stimulus-human observers-is assumed to decline with repeated exposure to that stimulus. We use habituation as a quasi-experiment to study the landscape of fear, exploring relationships between actual risk, perceived risk, mediating environmental variables, and behavioral correlates. Materials and Methods We recorded vocalizations and observer-directed vigilance as indicators of perceived risk during habituation of two troops of chacma baboons (Papio ursinus) in Gorongosa National Park, Mozambique. Here, we model changes in these variables as a function of habituation time, troop, time of day, and habitat features. We also model the relationship between each of the anti-predator behaviors and ground-use, exploring whether they predict greater terrestriality in the baboons. Results In both troops, vocalization rates and observer-directed vigilance declined with cumulative exposure to observers, but were heightened later in the day and in denser habitat types. We found that terrestrial activity was negatively related to levels of both vocalizations and observer-directed vigilance. Discussion This study provides a quantitative assessment of the impact of human observation on primate behavior and highlights environmental variables that influence anti-predator behaviors, perhaps indicating heightened perception of risk. The relationship between perceived risk and terrestriality is significant for understanding the evolution of this rare trait in primates.